Role of Single Walled Carbon Nanotube in Nanophase MgH2 Hydrogen Storage System - Iyakutti1, K.; Lavanya2, R.; Surya3, V.J.; Vasu2, V.; Kawazoe4, Y.; Izuseki5, H.M. (Asian Journal of Chemistry, 2013)
While the hydrogen storage property of bulk MgH2 is remarkable, the nanophase MgH2 is not completely understood. Wu et al. experimentally investigated the hydrogen storage properties of MgH2/single walled carbon nanotube composite systems and found that, while all the carbon additives acted as effective composite phase, Single-walled carbon nanotubes exhibited the most prominent catalytic function to enhance the hydrogen storage properties of MgH2. We wish to confirm this role of single walled carbon nanotube in MgH2/single walled carbon nanotube using first principles calculation. We functionalized single walled carbon nanotube with MgH2 and hydrogenated. It is found that one can get a hydrogen storage capacity of 5.0-6.4 wt % with the hydrogen binding energy around 0.3 eV, in this carbon nanotube-8MgH2 complex. Our study confirms that the carbon nanotubes neither act as catalysts nor as a component of the composite phase.